9x+10=-2(x+3)+3x

Simple and best practice solution for 9x+10=-2(x+3)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+10=-2(x+3)+3x equation:


Simplifying
9x + 10 = -2(x + 3) + 3x

Reorder the terms:
10 + 9x = -2(x + 3) + 3x

Reorder the terms:
10 + 9x = -2(3 + x) + 3x
10 + 9x = (3 * -2 + x * -2) + 3x
10 + 9x = (-6 + -2x) + 3x

Combine like terms: -2x + 3x = 1x
10 + 9x = -6 + 1x

Solving
10 + 9x = -6 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
10 + 9x + -1x = -6 + 1x + -1x

Combine like terms: 9x + -1x = 8x
10 + 8x = -6 + 1x + -1x

Combine like terms: 1x + -1x = 0
10 + 8x = -6 + 0
10 + 8x = -6

Add '-10' to each side of the equation.
10 + -10 + 8x = -6 + -10

Combine like terms: 10 + -10 = 0
0 + 8x = -6 + -10
8x = -6 + -10

Combine like terms: -6 + -10 = -16
8x = -16

Divide each side by '8'.
x = -2

Simplifying
x = -2

See similar equations:

| r^4=3r^3+18r^2 | | 10x+8=65+13x | | y^2=x+1 | | 12=-14B+3B | | 0.14-0.01(x-2)=-0.02(3-x) | | X-x(3x-5)=x-2(x(x)+x)-x(x)-14 | | S=2(3.14)rh+(3.14) | | y=14-2y | | -6-3=9r-6 | | 0.10(x+10)+0.70x=17 | | 4(2x-5)=3x+13 | | 10P+8=5P-2 | | 13-22=-3x | | 16-3b=0 | | 5=7Y-5Y-3 | | y^2+13y+12= | | 16-36=0 | | 10B-11B=0 | | 2(-4+p)=-8.2+1.8p | | -4=-9+8-29 | | x^2+47x+56=0 | | H(x)=2x^3+5x^2-31x-15 | | -15n^2+13=-10n^2-6n | | 6x(3x-4)(2x+5)= | | x^6-243=0 | | -4=9+8-29 | | 3n^2=-8 | | 51a-56=44 | | 4=9+8-29 | | 10v^7+26v^6+12v^5= | | (m-5)x^2-(m+2)x+(m-1)=0 | | -3(3s-3)-9=-2(8s+2)-2 |

Equations solver categories